Summative evaluation of online learning application: Comparative study - Berino, Dennis L. (Animo Repository, 2019)
The author has been doing online learning since 2007. It initially started with blended learning using available software and technology to enhance class discussion and engagement. The author eventually adopted a learning management system and started having fully online sessions (limited mixed mode) out of the total classroom sessions each term. Summative evaluation of this experience revealed favorable feedback among the students in terms of the exposure as well as the experience that the set up brought about. Starting this school year, 2015-2016, the author has adopted an expanded mixed mode class set up where 50% of the class sessions, the maximum allowed by the school where he teaches, are done online. This research study aims to compare the online learning experiences of students under a limited and expanded mixed mode online learning experience. The results show that although there were differences in the way benefits and difficulties in online learning were scored under limited and expanded mixed mode set ups, the differences are not statistically significant. Both sets of respondents scored their experiences favorably. The results of the study will be used to further enhance the delivery of learning and engagement of students under an online learning modality.